PENGARUH KOMPETENSI PEDAGOGIK GURU, PENDIDIKAN KARAKTER, DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR IPS DI SMP NASIONAL MALANG - Mado Lipat Goreti Maria; Endah Andayani; Naim Naim (Jurnal Riset Pendidikan Ekonomi, 2019)
This study aims to determine whether there is influence between teacher pedagogical competence, character education and learning facilities on social studies learning achievement in VIII grade of Malang National Junior High School and to find out how much influence between teacher pedagogical competence, character education and learning facilities on social studies learning achievement together with students of class VIII of Malang National Middle School. Total population of 116 samples used 47 students proportional random sampling. Data collection was conducted using a questionnaire and documentation method. This type of research uses a quantitative research approach. The method of multiple linear regression research. Hypothesis testing using t test and F test. The results of this study indicate that there is a significant influence of teacher pedagogical competence variables on social studies learning achievement of 6.522%. The significant influence of character education on social studies learning achievement is 43.65%. The significant influence of learning facilities on social studies learning achievement is 40.21%. Based on the results of the processed data test it can be seen that the variable pedagogical competence of teachers, character education and learning facilities has a simultaneous or joint effect on social studies learning achievement of 65,3%.